2014 21st IEEE International Conference on Electronics, Circuits and Systems (ICECS) 2014
DOI: 10.1109/icecs.2014.7049947
|View full text |Cite
|
Sign up to set email alerts
|

Sizing of the physical layer of a RF intra-chip communications

Abstract: In this paper we size a RF intra-chip communications based on Orthogonal Frequency Division Multiple Access (OFDMA) modulation which allows data rate and message recipient reconfiguration. Firstly, we present the advantages of this modulation such as providing flexible and high-speed data transmission. Then, we study the impact of the RF-interconnect channel shape on the transmission in terms of required transmission power. Finally, we present the effect of the channel composed of the line and its multiple acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Provided converter technology by our partner NXP envisions a 20 GHz bandwidth for the system. Based on the design constraints and circuit simulations, most suitable spectrum is chosen between 20-40 GHz (Hamieh et al, 2014). It is decided to have 1024 subcarriers, thus 1024point FFT and IFFT blocks are required.…”
Section: Ofdma Based Rf Interconnectmentioning
confidence: 99%
See 2 more Smart Citations
“…Provided converter technology by our partner NXP envisions a 20 GHz bandwidth for the system. Based on the design constraints and circuit simulations, most suitable spectrum is chosen between 20-40 GHz (Hamieh et al, 2014). It is decided to have 1024 subcarriers, thus 1024point FFT and IFFT blocks are required.…”
Section: Ofdma Based Rf Interconnectmentioning
confidence: 99%
“…It was shown that WiNoCoD interconnect has a 0.2-0.3 dB/mm attenuation with distance over 20-40 GHz band. These results are derived in the scope of WiNoCoD project (Briere et al, 2015;Hamieh at al., 2014).…”
Section: Ofdma Based Rf Interconnectmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, design and sizing of RF elements for RF-NoC architectures based on waveguides have already been proposed in the literature, demonstrating the feasibility of the approach. The interested reader could find more details in [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-hop paths replaced by single hop links [5], [8] Challenges thermal issue because of high-power density…”
Section: Introductionmentioning
confidence: 99%